An exergy-based analysis for the synthesis of aromatics from biomass - Mohammed Usman; Joseph Akintola; Gabriel Umoh; Joseph Akpan; Ekpotu Wilson; Queen Moses; Philemon Udom; Edose Osagie (Next Sustainability)
The chemical process industry has been facing rising energy costs, increasing competition due to rapid globalization, and more stringent government regulations amid growing public concern for the environment, health, and safety. In response to these challenges and considering the industry's capital-intensive nature, ongoing optimization through redesigning existing production plants has become a key strategy. This study designs and analyses a typical process plant with two routes for synthesizing aromatics from methanol and pentane. Process route 1 involves co-feeding, while process route 2 incorporates recycling and producing pentane. For methanol synthesis, cellulose (biomass) is used as the initial raw material, leading to the synthesis of aromatics through a reaction with pentanes. Exergy, exergo-economic, and pinch analyses are performed on both process routes. The routes display different overall exergy performances, with process routes 1 and 2 achieving 39.53 % and 25.43 % exergy, respectively. The highest exergetic performance is recorded in the CO2 heater (67.69 %) and the biomass oxidation reactor (88.70 %) for process routes 1 and 2, respectively. Exergo-economic evaluations indicate that Benzene distillation separation experiences exergy destruction rates of 28.61 % and exergo-economic factor of 99.92 % for process 1, while the aromatics heater shows the highest exergy destruction of 56.68 % for process 2. Implementing heat integration in the process routes reveals that process route 1 achieves energy savings of 92.09 %, while process route 2 results in 51.38 % energy savings. This study demonstrates the two process routes’ long-term economic viability and efficiency, which can be further optimised in future studies to achieve sustainable process implementation.